Correlation between structural properties and nonradiative recombination behaviors of threading dislocations in freestanding GaN substrates grown by hydride vapor phase epitaxy. Issue 48 (10th November 2020) - Yao, Yongzhao; Sugawara, Yoshihiro; Yokoe, Daisaku; Sato, Koji; Ishikawa, Yukari; Okada, Narihito; Tadatomo, Kazuyuki; Sudo, Masaki; Kato, Masashi; Miyoshi, Makoto; Egawa, Takashi
Abstract : Nonradiative recombination behaviors of threading dislocations and their correlation with the dislocation types. Abstract : Correlations between the structural properties and nonradiative recombination (NRR) behaviors of threading dislocations in freestanding hydride-vapor-phase-epitaxy (HVPE) GaN substrates were investigated using cathodoluminescence (CL), the etch pit method, transmission electron microscopy (TEM), and multiple-photon excitation photoluminescence (MPPL). A statistical analysis with a one-to-one comparison of 480 CL dark spots (prior to etching) with their corresponding etch pits shows that all dislocation types act as NRR centers with a strong correlation between the NRR rate at the dislocation cores and the pit size. Further TEM observations accurately determined the magnitude and direction of Burgers vectors for dislocations under each type of etch pit, which firmly links the NRR behaviors with the dislocation type. It is found that a dislocation pair composed of ( a + c ) and (− a + c ) threading mixed-type dislocations (TMDs) is the strongest NRR center among the considered dislocation types. The pair runs along the c -axis with a stable distance of 42 nm between them. This is followed by other types of TMD pairs, a + c TMDs, ma + nc TMDs ( m and n are integers, m > 1 or n > 1), 1 c threading screw dislocations, and 1 a threading edge dislocations in descending order of NRR rates. Three-dimensional (3D) dislocation images visualized by MPPL revealed that most of the dislocations are nearly parallel to the c -axis, while the a + c TMDs are susceptible to large tilting. MPPL also indicates that the ma + nc TMDs may result from several merging dislocations.